Regional patterns of manufacturing industries a study of manufacturing industries in Java region, Indonesia - Wahyudi, Setyo Tri; Jantan, Mohd Dan.
The paper aims to complement the findings of studies on regional and industrial concentration in Indonesia`s manufacturing industry by exploring whether regional specialization and industrial concentration patterns changed during the 1998-2007 period. In particular, the focus is on the three biggest regions in Java using Indonesia`s Standard Industrial Classification of Industries (SIC) at the three-digit level (SIC 151-293) on the basis of employment data by branch and by region. The major findings of the study show that during 1998-2007, Java`s region became more specialized and industry became more concentrated.
Keywords: Manufacturing industries -- Indonesia -- Java region